2020
DOI: 10.1093/biolre/ioaa224
|View full text |Cite
|
Sign up to set email alerts
|

The effects of assisted reproduction technologies on metabolic health and disease†

Abstract: The increasing prevalence of metabolic diseases places a substantial burden on human health throughout the world. It is believed that predisposition to metabolic disease starts early in life, a period of great susceptibility to epigenetic reprogramming due to environmental insults. Assisted reproductive technologies (ART), i.e., treatments for infertility, may affect embryo development, resulting in multiple adverse health outcomes in postnatal life. The most frequently observed alteration in ART pregnancies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 114 publications
0
23
0
2
Order By: Relevance
“…Growing evidence suggests that although the majority of children conceived through ART are healthy, they are at increased risk for several perinatal complications, birth defects, alterations in later body composition, metabolic and hormonal changes, and rare imprinting disorders [ 34 , 35 , 36 , 37 ]. Multiple exposures of ART occur at critical windows of development coinciding with global epigenetic reprogramming [ 38 ].…”
Section: Epigenetic Effect Of Maternal Methyl-group Donor Intake On R...mentioning
confidence: 99%
“…Growing evidence suggests that although the majority of children conceived through ART are healthy, they are at increased risk for several perinatal complications, birth defects, alterations in later body composition, metabolic and hormonal changes, and rare imprinting disorders [ 34 , 35 , 36 , 37 ]. Multiple exposures of ART occur at critical windows of development coinciding with global epigenetic reprogramming [ 38 ].…”
Section: Epigenetic Effect Of Maternal Methyl-group Donor Intake On R...mentioning
confidence: 99%
“…Covariates weight, smoking status, alcohol consumption, and education level are considered to be maternal factors that in uence body habitus of offspring [31][32][33] . Recently, it has been reported that assisted reproduction technology can affect metabolism in offspring 34,35 . Therefore, we included the following maternal covariates in the analysis: age during pregnancy, pre-pregnancy BMI, highest education level, annual household income, smoking status, alcohol consumption, pregnancy complications, obstetric complications, history of physical disease, parity, and use of assisted reproduction technology (i.e., in vitro fertilisation, intracytoplasmic sperm injection, fresh/frozen embryo transfer, and blastocyst transfer).…”
Section: Outcomementioning
confidence: 99%
“…Despite the fact that the majority of ART children are born healthy, there is concern about potential long-term consequences related to ovarian stimulation and in vitro culture techniques [ 5 ]. ART conception has been associated with adverse health outcomes such as preterm delivery, low birth weight, being small for gestational age or perinatal mortality [ 6 ]; cardiometabolic alterations [ 7 ]; and imprinting disorders, such as Beckwith–Wiedemann syndrome (BWS), Silver–Russell syndrome (SRS) and Prader–Willi syndrome (PWS) [ 8 ], although the extent to which ART procedures themselves or the underlying infertility of parents contribute is not fully understood. With the extended use of genome-wide approaches, more studies have focused on analyzing the global DNA methylation profile in children conceived by ART.…”
Section: Introductionmentioning
confidence: 99%